Protective effect of HwangRyunHaeDok-Tang water extract against chronic obstructive pulmonary disease induced by cigarette smoke and lipopolysaccharide in a mouse model. (22nd March 2017) - Shin, Na-Rae; Ko, Je-Won; Park, Sung-Hyeuk; Cho, Young-Kwon; Oh, Sei-Ryang; Ahn, Kyung-Seob; Ryu, Jung-Min; Kim, Jong-Choon; Seo, Chang-Seob; Shin, In-Sik
Abstract: Ethnopharmacological relevance: Hwangryunhaedok-tang is an oriental herbal formula treated to cure inflammation and gastric disorders in China, Japan, and Korea. We explored the protective effects of Hwangryunhaedok-tang water extract (HRWE) against airway pathophysiological changes caused by cigarette smoke (CS) and lipopolysaccharide (LPS) in a mouse. Materials and methods: We performed quantitative analyses of five marker components, namely geniposide, baicalin, coptisine, plamatine, and berberine, using high-performance liquid chromatography. Animals were received CS exposure (1 h per day) for 7 days. LPS was administered intranasally on day 4. Mice were received HRWE at dose of 100 or 200 mg/kg for 1 h before CS exposure. Results: Treatment with HRWE significantly suppressed the increased inflammatory cell count induced by CS and LPS exposure. In addition, reduction in IL-6, TNF-α and IL-1β in broncho-alveolar lavage fluid (BALF) was observed after HRWE treatment. HRWE not only decreased inflammatory cell infiltration in lung, but also decreased the expression of iNOS, NF-κB and matrix metallopeptidase (MMP)-9 in lung tissues. Conclusion: This study showed that HRWE can attenuate respiratory inflammation caused by CS and LPS exposure. Therefore, HRWE has potential for treating airway inflammatory disease. Graphical abstract: